Moving toward wellbeing: physical activity and quality of life in individuals with physical disabilities in Saudi Arabia - Alhumaid, Majed M.; Said, Mohamed A. (Frontiers in Psychology, 2025)
Background and objectivesThis study examined the associations between quality of life (QoL) and physical activity (PA), self-perceived health and fitness, and sociodemographic characteristics among individuals with physical disabilities (IWPDs) in Saudi Arabia.Materials and methodsA total of 230 IWPDs aged 18 years and older participated in the study, comprising 133 males (57.8%) and 97 females (42.2%). QoL was assessed using the World Health Organization Quality of Life–Disabilities module, while PA levels were measured using the Arabic version of the Physical Activity Scale for Individuals with Physical Disabilities. Structural equation modeling was used to examine the relationships of overall PA and its specific domains—household, recreational, vocational, and home-repair activities—with overall QoL and its subdomains.ResultsSelf-perceived health and fitness were identified as the strongest correlates of both overall and domain-specific QoL. Education and income were positively associated with multiple QoL components—participants with higher education levels reported significantly greater Discrimination (β = 0.141), Autonomy (β = 0.236), and Inclusion/Participation (β = 0.29) but lower social relationships (β = −0.336). While total PA was not significantly associated with overall QoL, specific PA domains showed nuanced effects; For example, household activities were positively associated with the psychological domain (β = 0.25), social relationships (β = 0.542), environmental domain (β = 0.149), and autonomy-related domain (β = 0.531), but were negatively associated with physical health (β = −0.336) and inclusion/participation (β = −0.399). In contrast, home repair activities exhibited the opposite pattern. Sex differences were also observed, with men reporting lower QoL than women across several domains.ConclusionsThese findings underscore the relevance of health, education, employment, and psychosocial factors for QoL among IWPDs and provide insights that may inform future research as well as evidence-based health and disability policy planning in Saudi Arabia.